PELATIHAN TEKNIK PENULISAN PENELITIAN TINDAKAN KELAS PADA GURU PPKn MTs DI KABUPATEN PONOROGO - Prihma Sinta Utami; Sutrisno Sutrisno (IKIP PGRI Bojonegoro, 2017)
The government program in establishing the Teachers Subject (MGMP) forum in each district is a forum for subject teachers to exchange information on the latest policies and programs of the government. Regulation of Permendiknas No 35/2010 regarding technical guidance on the implementation of functional position of teachers which one of the requirements must conduct Classroom Action Research (PTK) becomes one of the problems for teachers of MGMP PPKn especially in Kabupaten Ponorogo. This is supported by the low interest of teachers in making Classroom Action Research caused by a lack of understanding about the making of the PTK itself. The purpose of this PKM activity is to provide a general overview of the steps of the implementation of PTK activities that lead to the subjects of PPKn in particular and provide mentoring classes in the making of PTK proposals. Method of implementation of activities undertaken in this PKM activity is the main implementation of the training workshop making of PTK as well as conducting a class of assistance making the PTK proposal. The results of this activity include: 1) Obtaining titles of PTK submitted by teachers MGMP PPKn Ponorogo District; 2) PTK proposal from teachers of MGMP PPKn Kabupaten Ponorogo; 3) The results of the presentation of proposals for some teachers MGMP PPKn Ponorogo District and improvements together in the classroom.Keyword: Classroom Action Research, MGMP, PPKn SubjectÂ ABSTRAKProgram pemerintah dalam membentuk forum Musyawarah Guru Mata Pelajaran (MGMP) di setiap kabupaten merupakan satu wadah bagi guru mata pelajaran untuk bertukar informasi tentang kebijakan dan program-program terbaru dari pemerintah. Adanya tuntutan peraturan Permendiknas No 35/2010 tentang petunjuk teknis pelaksanaan jabatan fungsional guru yang salah satu persyaratannya harus melakukan Penelitian Tindakan Kelas (PTK) menjadi salah satu problema bagi guru-guru MGMP PPKn khususnya di Kabupaten Ponorogo. Hal ini didukung dengan rendahnya minat guru dalam pembuatan Penelitian Tindakan Kelas yang disebabkan oleh pemahaman yang kurang tentang pembuatan PTK itu sendiri. Tujuan dari kegiatan PKM ini adalah memberikan gambaran secara umum tentang langkah-langkah pelaksanaan kegiatan PTK yang mengarah pada mata pelajaran PPKn khususnya serta menyediakan kelas pendampingan dalam pembuatan proposal PTK. Metode pelaksanaan kegiatan yang dilakukan dalam kegiatan PKM ini yang utama adalah pelaksanaan kegiatan workshop pelatihan pembuatan PTK serta melakukan kelas pendampingan pembuatan proposal PTK. Hasil dari kegiatan ini antara lain: 1)Memperoleh judul-judul PTK yang diajukan oleh guru-guru MGMP PPKn Kabupaten Ponorogo; 2) Proposal PTK dari guru-guru MGMP PPKn Kabupaten Ponorogo; 3) Hasil presentasi proposal bagi beberapa guru MGMP PPKn Kabupaten Ponorogo serta perbaikan secara bersama di dalam kelas.Kata Kunci: Penelitian Tindakan Kelas, MGMP, Mata Pelajaran PPKn